Pengaruh Media Big book Bermuatan Cerita Rakyat Bima La Hila terhadap Kemampuan Membaca Permulaan Siswa Kelas III di SDN 11 Kempo - Andriani; Moh. Irawan Zain; Hasnawati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Reading is one of the basic skills that elementary school students must master. However, many students in the early grades still struggle with early reading, so innovative and engaging learning materials are needed to support the learning process. This study aims to determine the effect of using a Big book containing the Bima folktale “La Hila” on the early reading skills of third-grade students at SDN 11 Kempo. This study employed a quantitative approach with a quasi-experimental design using a Nonequivalent Control Group Design. The study population consisted of 26 students, comprising 13 students in the experimental class and 13 students in the control class. Data collection techniques included pre-tests and post-tests, while data analysis was conducted using descriptive statistics, normality tests, homogeneity tests, and an Independent Samples t-test. The results showed that the experimental class’s pre-test mean score of 68.92 increased to 89.46 on the post-test, while the control class’s score increased from 63.92 to 80.00. The results of the normality test showed that the data were normally distributed, and the homogeneity test indicated that the data were homogeneous with a significance value of 0.978 > 0.05. Furthermore, the results of the independent samples t-test showed a significance value of 0.000 (< 0.05) and a calculated t-value of 4.294, which was greater than the critical t-value of 2.064. Thus, H₀ is rejected and Hₐ is accepted, leading to the conclusion that the use of Big book media containing the Bima folktale “La Hila” has a positive and significant effect on students’ early reading skills. The findings of this study indicate that integrating local folktales into Big book media is not only effective in improving early reading skills but can also foster students’ appreciation for local culture.